Expressão de genes relacionados à remodelação óssea na fase inicial da reabsorção do rebordo residual em mandíbulas humanas - Zutin, Elis Andrade de Lima [UNESP] (2013)
The understanding of residual ridge resorption (RRR) can provide an important scientific basis for improving restorative and therapeutic treatments of edentulous patients. The present study aimed to seek molecular markers involved in bone remodeling in bone tissue from jaws that suffered the extraction of remaining teeth in less than two months period (in which the RRR is more intense).The group of samples analyzed in this study was composed of five individuals who underwent tooth extraction operated in less than two months by area and one patient who underwent tooth extraction operated in the area for more than five years , which was used as calibrator. All patients had their recorded clinical data and panoramic radiographs of patients was used to perform set for evaluation of anatomical features previously related to RRR. The RNA samples were extracted and presented purity between 1.8 and 2.0. The preparation of cDNA was performed by qRT-PCR. For quantitative analysis, all reactions were performed at optical plates 96 wells for specific real-time PCR using primers of 40 genes involved in bone metabolism. Taking into account the level of expression and the lowest variation among the reference genes, HPRT1 was chosen as the normalizing gene. The mean age of subjects was 53.8 ± 5.6 years and only one of the subjects were female. In all samples, the greater presence of target genes underexpressed (green), followed by overexpressed (red) and moderately expressed (black) occurred. Intense activity of bone remodeling was observed in patients with initial bone remodeling, which had great individual heterogeneity in gene expression of bone formation and resorption. However, no significant correlations between clinical and laboratory findings for this group of patients